A large deletion in RPGR causes XLPRA in Weimaraner dogs. Issue 1 (December 2016) - Kropatsch, Regina; Akkad, Denis; Frank, Matthias; Rosenhagen, Carsten; Altmüller, Janine; Nürnberg, Peter; Epplen, Jörg; Dekomien, Gabriele
Abstract Background Progressive retinal atrophy (PRA) belongs to a group of inherited retinal disorders associated with gradual vision impairment due to degeneration of retinal photoreceptors in various dog breeds. PRA is highly heterogeneous, with autosomal dominant, recessive or X-linked modes of inheritance. In this study we used exome sequencing to investigate the molecular genetic basis of a new type of PRA, which occurred spontaneously in a litter of German short-hair Weimaraner dogs. Results Whole exome sequencing in two PRA-affected Weimaraner dogs identified a large deletion comprising the first four exons of the X-linked retinitis pigmentosa GTPase regulator(RPGR) gene known to be involved in human retinitis pigmentosa and canine PRA. Screening of 16 individuals in the corresponding pedigree of short-hair Weimaraners by qPCR, verified the deletion in hemizygous or heterozygous state in one male and six female dogs, respectively. The mutation was absent in 88 additional unrelated Weimaraners. The deletion was not detectable in the parents of one older female which transmitted the mutation to her offspring, indicating that theRPGR deletion represents ade novo mutation concerning only recent generations of the Weimaraner breed in Germany. Conclusion Our results demonstrate the value of an existing DNA biobank combined with exome sequencing to identify the underlying genetic cause of a spontaneously occurring inherited disease. Identification of the genetic cause has allowed the development of a diagnostic test, which should help to eradicate the PRA causing mutation from the respective canine line. Thus, planning of future pairings is facilitated and manifestation of this type of PRA can be prevented.